ANALISIS PERILAKU KURS RUPIAH (IDR) TERHADAP DOLLAR AMERIKA (USD) PADA SISTEM KURS MENGAMBANG BEBAS DI INDONESIA PERIODE 1997.3 – 2011.4 (APLIKASI PENDEKATAN KEYNESIAN STICKY PRICE MODEL) - Tara Eka Pratiwi; H. Purbayu Budi Santosa Santosa (Universitas Diponegoro, 2012)
Currency stability is an important issue to boost economic activity and create economic growth of a country. Trade between countries resulting in currency exchange rates between countries are reflected in the exchange rate. The importance of the role of exchange rates for both developed and developing countries, encourage efforts to keep the exchange rate of a country is in a relatively stable state. The stability of the currency exchange rate is also affected by the exchange rate system adopted by a country. The phenomenon that often occurred in connection with the exchange rate fluctuations in currency values ​​is uncertain. Changes in behavior Rupiah exchange rate against the U.S. dollar that occurred in Indonesia during the period 1997.3 to 2011.4 on the implementation of a free-floating exchange rate system (free floating exchange rate system) are affected by economic fundamentals and non-fundamental economic factors. The aim of this research is to analyze how and how much influence factor relative GDP, the relative JUB, the Interest Rate and the CPI relative to relative changes in the behavior of Rupiah exchange rate against the U.S. dollar. The results of the analysis including the variable M2, the interest rate and the CPI has a positive and significant impact on the exchange rate, GDP variables possess a negative and significant relationship to the exchange rate.